In Silico Evaluation of the Binding Site of Fucosyltransferase 8 and First Attempts to Synthesize an Inhibitor with Drug‐Like Properties. (24th September 2019) - Strecker, Claas; Baerenfaenger, Melissa; Miehe, Michaela; Spillner, Edzard; Meyer, Bernd
Abstract: Core fucosylation of N ‐glycans is catalyzed by fucosyltransferase 8 and is associated with various types of cancer. Most reported fucosyltransferase inhibitors contain non‐drug‐like features, such as charged groups. New starting points for the development of inhibitors of fucosyltransferase 8 using a fragment‐based strategy are presented. Firstly, we discuss the potential of a new putative binding site of fucosyltransferase 8 that, according to a molecular dynamics (MD) simulation, is made accessible by a significant motion of the SH3 domain. This might enable the design of completely new inhibitor types for fucosyltransferase 8. Secondly, we have performed a docking study targeting the donor binding site of fucosyltransferase 8, and this yielded two fragments that were linked and trimmed in silico. The resulting ligand was synthesized. Saturation transfer difference (STD) NMR confirmed binding of the ligand featuring a pyrazole core that mimics the guanine moiety. This ligand represents the first low‐molecular‐weight compound for the development of inhibitors of fucosyltransferase 8 with drug‐like properties. Abstract : Structure‐based ligand discovery : Fucosyltransferase 8 catalyzes the core fucosylation of N ‐glycans. Here, we have performed an in silico analysis of a new putative binding site of fucosyltransferase 8. We also describe the design and synthesis of a donor‐site binder to start the development of inhibitors of fucosyltransferase 8 with drug‐like properties.